The Constitutional Position of the Federal Council (Bundesrat) in the German Political System - Al-Najjar, Sherzad Ahmad Ameen; Majed, Dlawar Osman (Journal of Legal and Political Studies, 2019)
The Federal Council (Bundesrat) represents all of the German Landers and expresses the federal constituents of the federal state. It is also composed of members sent by Lander governments. Through the Council, Landers are involved in the drafting of laws, legislation and administration of the German Federal State affairs. According to the constitutional center occupied by the Council of States in the constitutional structure of the State, it cannot be considered an institution of the regions; it is a federal body exercises only federal powers. Taking the various party political formations into account in the Union and the states, the Council of the States can achieve some kind of political balance, as it can be used as an opposition tool to hamper the political work of the federal government, and as such limit the ability of the federal government to pass laws easily.
Keywords: Constitutional Position; Federal Council; Bundesrat; Constitution; Germane